Adjuvant endocrine therapy in patients with estrogen receptor-low positive breast cancer: A prospective cohort study. (December 2022) - Xie, Yuxin; Yang, Libo; Wu, Yanqi; Zheng, Hong; Gou, Qiheng
Abstract: Background: Little is known about the benefits of adjuvant endocrine therapy (ET) in low ER-positive breast cancer (1%–10%) patients. We analyzed the association between ET and breast cancer-specific survival (BCSS) in these patients with respect to the regimen and the duration of ET. Methods: Patients were classified into three groups based on the regimen and duration of ET. The regimens included aromatase inhibitor (AI) monotherapy or sequential tamoxifen followed by an AI (AI/T + AI), or only tamoxifen and no ET. The duration of ET included 2–3 years and >3 years. Multivariate Cox regression analysis was employed to calculate the hazard ratios (HRs) with 95% confidence intervals (CIs). Results: Of the 10, 696 patients diagnosed with breast cancer between 2010 and 2020, 407 women were identified with ER-low positive disease and met the inclusion criteria. During a median follow-up of 5.2 years, patients who received ET improved BCSS. Of them, those with AI/T + AI had increased BCSS compared to patients without ET, after adjusting for demographics and tumor characteristics, especially in ER-low/HER-2-positive breast cancer. After additional adjustment for treatment mode, the association maintained a similar trend. Patients who received >3 years of ET was associated with a better DFS. There was no significant difference in BCSS between patients with 2–3 years and >3 years of ET. Conclusion: For ER-low patients, findings suggest that ET with AI/T + AI may be a reasonable treatment alternative. This effect should be assessed in randomized studies. Highlights: Patients with mono- or sequential aromatase inhibitor therapy have better survival. It seems that >3 years of adjuvant ET should be standard for ER-low patients. Aromatase inhibitor is an option for low estrogen receptor-positive breast cancer.